G524 The teen health talk – a feasibility study in the use of a biopsychosocial assessment tool for adolescents in primary care. (25th October 2020) - Lamb, S; Hagell, A; Wolfe, I
Abstract : Aims: The Teen Health Talk (THT) is a biopsychosocial assessment tool developed to promote better health assessments for young people (YP) at a young person's health hub. The aim was to assess the feasibility of using an abridged version in routine practice in Primary Care. Method: The THT is recorded on a template on a GP data system, EMIS, and provides prompts to the GP to help them conduct an effective adolescent consultation. The template was exported to 3 pilot sites (GP Practices) and each site was visited by the GP who developed the tool and clinicians were trained in the use of it. It was then trialled for 8 weeks. In addition focus groups were held with 2 groups of young people (n=25) to assess their opinion of the acceptability and utility of the THT. Results: 2 of the practices completed 51 THT between them. 1 practice did not complete any. The pilot centres who used the THT agreed it was useful and improved the focus on this age group in addition to improving communication. They commented it was feasible to use it within a 10 minute consultation and was also a useful training tool for junior staff. Young people were positive about a professional taking an interest in their health beyond the presenting complaint and agreed the topics covered were relevant and important. Conclusions: Primary care staff and young people confirmed that the THT is an important and useful assessment tool that can be used in primary care. Practices need support and training in how to use the tool and also confidence in what to do with the information uncovered – this requires knowledge about local resources and referral pathways and would benefit from the development of accompanying materials. Wider dissemination would potentially improve young people's experience of primary care leading to better utilisation in addition to the health benefits of earlier intervention and prevention where appropriate.